2006
DOI: 10.1063/1.2136788
|View full text |Cite
|
Sign up to set email alerts
|

On the epitaxy of twin-free cubic (111) praseodymium sesquioxide films on Si(111)

Abstract: Twin-free epitaxial cubic (111) praseodymium sesquioxide films were prepared on Si(111) by hexagonal-to-cubic phase transition. Synchrotron radiation grazing incidence x-ray diffraction and transmission electron microscopy were applied to characterize the phase transition and the film structure. As-deposited films grow single crystalline in the (0001)-oriented hexagonal high-temperature phase of praseodymium sesquioxide. In situ x-ray diffraction studies deduce an activation energy of 2.2eV for the hexagonal-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 35 publications
0
42
1
Order By: Relevance
“…7 Postdeposition annealing in 10 −5 mbar O 2 transforms h-Pr 2 O 3 films into cubic c-Pr 2 O 3 films with bixbyite structure ͑Ia3͒ which are stable if exposed to air. 8 The bulk lattice constant of c-Pr 2 O 3 is approximately twice the bulk lattice constant of Si. The residual lattice mismatch is +2.6% taking into account the 2:1 relationship of the lattice constants.…”
mentioning
confidence: 99%
“…7 Postdeposition annealing in 10 −5 mbar O 2 transforms h-Pr 2 O 3 films into cubic c-Pr 2 O 3 films with bixbyite structure ͑Ia3͒ which are stable if exposed to air. 8 The bulk lattice constant of c-Pr 2 O 3 is approximately twice the bulk lattice constant of Si. The residual lattice mismatch is +2.6% taking into account the 2:1 relationship of the lattice constants.…”
mentioning
confidence: 99%
“…This explains the phase transition one observes when hexagonal Pr 2 O 3 , which is our original phase after the evaporation process, is transformed to twin-free cubic Pr 2 O 3 or Pr 2 O 3+␦ by annealing in nitrogen 11 or low pressure oxygen. 12 The phase transition and the formation of an interface layer were not observed after annealing in UHV. 11 If the substrate was oxidized before the evaporation process, the film grows in the cubic phase but with a high density of stacking twins.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the phase transition is only observed after an interfacial layer was formed between film and substrate. 12 This has been interpreted as a disconnection of film and substrate. 12 As we observed that the lateral lattice constant does not change significantly during the annealing process, this disconnection cannot be the reason for the phase transformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations